Core Attributes of Stewardship; Foundation of Sound Health System - Neelesh Kapoor; Dewesh Kumar; Nivedita Thakur (Kerman University of Medical Sciences, 2014)
Stewardship is not a new concept for public policy, but has not been used to its optimum by the health policy-makers. Although it is being practiced in most successful models of health system, but the onus to this function is still due till date. Lately, few experts in World Health Organization (WHO) have realized its importance and have been raising the issue at different platforms to pursue the most important function of the health system i.e. stewardship. These core attributes of stewardship need to be understood in totality for better understanding of the concept. The core attributes required for hassle free functioning of a health system include responsible manager, political will, normative dimension, balanced interventionist and proponents of good governance.